Talus partitus. Kazuistika - Chandoga, Ilja; Vajcziková, Silvia (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2012)
An ankle bone consisting of several fragments is a rare anatomical variant of the talus, in the literature described as talus partitus or frontal split. On radiographs or CT scans it presents as two or more relatively large fragments. The term talus partitus is sometimes incorrectly used for an accessory bone that occasionally develops behind the ankle bone and is called os trigonum. talus partitus is an unusual developmental anomaly in which the talus is partitioned although it ossifies from a single centre. The cause of its split has not been explained although this may also be due to a previous unrecognized injury. In the Slovak medical literature no report of this anomaly has been found. Here we resent the case of a 30-year-old man in whom the ankle bone split was an incidental finding. This patient also had ipsilateral developmental dysplasia of the hip. This is the first report of a patient with the two concurrently found anomalies.
Keywords: Talus; dospělí; vývojová kyčelní dysplazie; Foot Deformities, Congenital; lidé; talus; mužské pohlaví; Male; Hip Dislocation, Congenital; Adult; vrozené deformity nohy (od hlezna dolů); Humans